Evaluation of reference genes and normalization strategy for quantitative real-time PCR in human pancreatic carcinoma - Mohelnikova-Duchonova, Beatrice; Oliverius, Martin; Honsova, Eva; Soucek, Pavel (Disease markers, 2012)
Histologically verified pairs (n=10) of pancreatic tumors and non-neoplastic tissues were used for quantitative real-time PCR and the stability of 24 reference genes was analyzed with geNorm and NormFinder software. Raw Cq values correlated with the degree of RNA degradation. This correlation was abolished by normalization to Cq of 18S endogenous control gene. Both geNorm and NormFinder programs suggested EIF2B1, ELF1, MRPL19, and POP4 as the same most stable genes. We have thus identified suitable reference genes for future expression studies in pancreatic carcinoma. Normalization method reducing the effects of RNA degradation on the quality of results was also developed.
Keywords: Eukaryotic Initiation Factor-2B; Male; pankreas; nádory slinivky břišní; lidé středního věku; Pancreas; karcinom; nádorové biomarkery; ribonukleoproteiny; Software; stanovení celkové genové exprese; Humans; Ribosomal Proteins; Pancreatic Neoplasms; exprese genu; Middle Aged; Biomarkers, Tumor; senioři; Transcription Factors; mužské pohlaví; mitochondriální proteiny; Female; software; Carcinoma; eukaryotický iniciační faktor 2B; RNA Stability; Aged; stabilita RNA; Mitochondrial Proteins; ženské pohlaví; ribozomální proteiny; Gene Expression; jaderné proteiny; transkripční faktory; Gene Expression Profiling; Nuclear Proteins; Ribonucleases; Real-Time Polymerase Chain Reaction; kvantitativní polymerázová řetězová reakce; lidé; Ribonucleoproteins; ribonukleasy